Adopting task technology fit model on e-voting technology - Asti Ratnasari; Avrillaila Akbar Harahap; Adib Arsyad Anshori; Mumtazul Alam (Institute of Advanced Engineering and Science, 2021)
E-voting is a tool to support the voting process starting from recording, voting, and counting votes using electronic devices. E-voting promises a faster voting process, reduced budget costs, lost votes due to damaged ballot papers during the voting process, and others. E-voting is also used in high school student council elections. Young people are more computer literate (computer literacy) and interested in using new technology (e-voting) than adults and older people. This study aims to determine the suitability of e-voting in the SMA OSIS election to the user's task support using the task-technology fit (TTF) model. The data analysis used is multiple regression analysis. This analysis is used to determine the effect of the independent variables on the dependent variable with a significance level of 5%. The results of this study indicate that the 4 formulated hypotheses can be accepted and the students of SMK Muhammadiyah 1 Bantul feel the suitability of technology support when voting using e-voting in the selection of the high school student council.